Effects of R&D spending on innovation by Irish and foreign-owned businesses - Doran, Justin; Jordan, Declan; O?Leary, Eoin (Statistical and Social Inquiry Society of Ireland, 2013)
This paper estimates the private returns to four different kinds of R&D spending on the probability of Irish and foreign-owned businesses engaging in product, process and organizational innovation. By providing econometric analysis of nearly 2000 businesses in the Community Innovation Survey: 2004 to 2006, it makes an important contribution to our understanding of the effects of Irish innovation policy, which has incentivized businesses to spend on R&D in Ireland. The main findings are that Irish-owned businesses are significantly more likely than foreign-owned to introduce new products as a result of creative R&D work undertaken. Foreign-owned businesses, which spend nearly 6 times more per worker on R&D than Irish-owned, enjoy very high returns mostly from the purchase or licence of patents. This reflects a fundamental difference in the innovation activities of these businesses, which is critical for policymakers? understanding of the Irish innovation system.
Keywords: innovation policy; innovation output; Research & Development; 314.15